Sardine in outer space. 05 - Guibert, Emmanuel (First Second, 2008)
Presents more adventures of the mischievous girl pirate named Sardine, as she and the crew of the spaceship "Huckleberry" foil the plans of evildoers Supermuscleman and Doc Krok.